The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.36636/psikodinamika.v1i2.732
|View full text |Cite
|
Sign up to set email alerts
|

Regulasi Emosi terhadap Resiliensi atlet Pencak Silat

Abstract: Penelitian ini mengkaji tentang pengaruh Regulasi Emosi Terhadap Resiliensi Atlet Pencak Silat Tapak Suci Gresik. Regulasi emosi adalah cara atlet dalam mengelola emosi dan menyeimbangkan dengan keadaan yang sulit sehingga atlet mampu merubah emosi negatif menjadi lebih positif. Resiliensi adalah kemampuan atlet dalam beradaptasi dari situasi atau masalah yang sedang dialami, kemampuan untuk bertahan, tidak mudah menyerah dan kemampuan untuk bangkit menyelesaikan permasalahan. Penelitian ini menggunakan metode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In completing a series of training activities, youth athletes are also focused and willing to follow the directions given. This is in line with research conducted by Paulana et al (2021), namely when adolescent athletes have good emotional regulation, they are able to refrain from expressing their emotions which can interfere with their focus and perseverance in completing a task.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In completing a series of training activities, youth athletes are also focused and willing to follow the directions given. This is in line with research conducted by Paulana et al (2021), namely when adolescent athletes have good emotional regulation, they are able to refrain from expressing their emotions which can interfere with their focus and perseverance in completing a task.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to achievement motivation, emotional regulation affects pre-match anxiety, where adolescent athletes who have good emotional regulation will be able to suppress tension caused by a lot of pressure (Angreini et al, 2021). In other studies, it was found that good emotional regulation will make adolescent athletes able to control when they have to express their emotions so that they can minimize the disruption of focus in achieving goals and can rely on themselves when competing (Paulana et al, 2021).…”
Section: A B S T R a Kmentioning
confidence: 99%
“…In addition, the results of previous research also reveal that there are differences in self-resilience between athletes who excel and do not excel (Rahmawati, 2020). Basically, resilience is needed for athletes because resilience is one of the supporting elements in exporting experiences from the difficulties faced, for example, due to injury, downturn, and career transition, Galli and Vealey (Paulana et al, 2021). Resilience is one of the important factors for athletes to reach the highest achievement in their sporting career because resilience has a significant relationship with athlete achievement (Khoirunnia' & Jannah, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some athletes have difficulty conducting self-evaluations after a loss. Poor performance to injury (Paulana et al, 2021). For athletes who excel, how do they make peace with themselves?…”
Section: Introductionmentioning
confidence: 99%